Sinergitas Kabinet Presidensiil Multipartai pada Masa Pandemi Covid-19 di Indonesia - Tundjung Herning Sitabuana; Ade Adhari (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
Implement the simultaneous election in Indonesia has supported by the multiparty system. The multiparty system has an impact on the President’s leadership. In the formation of the cabinet, the President must accommodate political party coalition interest. One form of that accommodations occurs of the minister which came from the coalition political party. Different from the minister's interest background has an impact on the different policies each minister especially on COVID-19 handler in Indonesia. The research method is normative research with a case approach and concept approach. This research used secondary data that used primary, secondary, and tertiary materials. This research shows that the presidential cabinet in Indonesia is a cabinet which forms by multi-party coalitions. On multiparty coalition implementation of Kabinet Indonesia Maju 2019-2024, there were several times, the minister has different policy among the minister or with local governments such as the case of the ban on taking passengers for online biking and prohibition against homecoming. Different policies among the minister or with local government can be minimized by the President’s political leadership.